"Pushing the Button While Pushing the Argument": Motor Priming of Abstract Action Language. (24th November 2016) - Schaller, Franziska; Weiss, Sabine; Müller, Horst M.
Abstract: In a behavioral study we analyzed the influence of visual action primes on abstract action sentence processing. We thereby aimed at investigating mental motor involvement during processes of meaning constitution of action verbs in abstract contexts. In the first experiment, participants executed either congruous or incongruous movements parallel to a video prime. In the second experiment, we added a no‐movement condition. After the execution of the movement, participants rendered a sensibility judgment on action sentence targets. It was expected that congruous movements would facilitate both concrete and abstract action sentence comprehension in comparison to the incongruous and the no‐movement condition. Results in Experiment 1 showed a concreteness effect but no effect of motor priming. Experiment 2 revealed a concreteness effect as well as an interaction effect of the sentence and the movement condition. The findings indicate an involvement of motor processes in abstract action language processing on a behavioral level.